Evaluation of inclusive education at Quantum Preschool - hiffzah roudhoh (Universitas Pendidikan Ganesha, 2018)
Abstract: This research is aimed at evaluating the inclusion educational program at Quantum Preschool, East Bekasi. Method of research applies mix method by designing CIPP model (Context, Input, Process, Product). The instrument of research utilizes a written guideline by means of observation and interview. Data are collected in accordance with the design of CIPP model. Subsequently, the data are analyzed quantitatively and qualitatively. The result of evaluation (1) percentage of implementation of component for context, the institutional background is 100% and learning atmosphere is 98.5%. Quantum Preschool has its own vision, mission, objective, status of institution, learning atmosphere, and curriculum since the year of 2007 (2) percentage of component for input, own facility infrastructure is 18.16%. The lack faced by the preschool is non availability of parking area for parents, curriculum is 100%, percentage of educating staff is 62.5% because some teacher do not have the background of Early Childhood Education, educational participants is 57.14%, financing is 92.8%, support of parents is 92% (3) percentage of component for process: planning is 100%, implementation is 92.5%, assessment is 90%, program development is 98.% (4) percentage of component: long-term program is 100% and short-term program is 82%. Keywords: Program evaluation, Inclusion, Early Childhood